Uso de fertilizantes de liberação lenta no estabelecimento de mudas de ipê roxo e angico branco em área de domínio ciliar - Lang, Aletéia (2008)
The use of fertilizers of controlled liberation is made one of the modern techniques in the raising of Young plants. However, there are few reports of its effects on the growing in native forest species in the area of ciliar dominion. It has been aimed to try different fertilizers of controlled liberation with a convencional fertilizer in the establishment of young in the field of Anadenanthera colubrine and Tabebuia avellanedae. The young plants were taken from the municipal nursey of Palotina-Pr, and they were planted in an area of ciliar dominion, by fertilization in the hole, with Basacote 3M, Basacote 6M, Basacote 9M, mineral manure in the formulation 16-08-12 (N, P2O5, K2O) with dose of 55 grams in each hole and witness. The experiment was conducted by outlining casual blocks, with subdivided portions, in which the factors were made by three treatments of Basacote, one of mineral manure and witness. It was evaluated the following features: diameter of the coleto length, number of leaves, foliar area, dried biomass of the root, dried biomass area, length of the root, and average of Dickson`s. Along 90 days of cultivation, the tested fertilization Basacote 3M influenced on the increment of the diameter of the coleto off Anadenanthera colubrine. With the increments of the length there was statistical difference amoing the species, with larger average (58, 96 cm) for the young plants of Tabebuia avellanedae and smaller average (48,70cm) to Anadenanthera colubrine. For the number of leaves, youngs plants of Anadenanthera colubrine showed better averages (150, 30). After 180 days of the plantations the young plants which received the treatment Basacote 9M, got larger average (113,37). Whereas, after 270 days of the plantation, the species Tabebuia avellanedae, got better results to the Basacote 3M in increments of the length. In the 360 days of the plantation, the differences happened among the with bigger increments off coleto (7,48mm) to young plants of Tabebuia avellenedae. The destructive analyses dried biomass of root, didn t answer the treatments, showing difference between the species with larger average to Tabebuia avellanedae. Dried biomass of the airy part, both the species didn t answer the treatments. The length of the root, answered in a negative way to the treatments, where it happened differences only among the species with larger average to young plants off Anandenanthera colubrine. To variable foliar area, only after the 360 days off the plantation, young plants off Tabebuia avellanedae, showed larger average, without interference off the treatments. On the Dickson s, both species didn t suffer big affects